A Comparative Analysis of Information Communication Technologies Development: A Study of Azerbaijan and Balkan Countries - Ibrahim Niftiyev (Canadian Institute of Technology, 2023)
Development of information and communication technologies (ICTs) plays a pivotal role in promoting overall technological progress in a nation and enabling transformative changes in various sectors. By providing a solid foundation for digital infrastructure, ICTs facilitate innovation, increase productivity, and spur economic growth, placing a nation at the forefront of the global technological landscape. The main objective of this study is to compare Azerbaijan's ICTs development with that of Balkan countries. The growing cooperation between Azerbaijan and the Balkan countries is primarily focused on the energy sector, but there is limited understanding of the technological similarities and differences. To further enhance this cooperation, a comprehensive study of the technological infrastructure and the identification of areas of convergence and divergence are essential. This study will facilitate informed decision-making, pave the way for expanded cooperation in various sectors beyond the energy sector, and promote mutually beneficial relations between Azerbaijan and the Balkan countries. The results of this study, based on hierarchical cluster analysis (HCA), show that Azerbaijan is similar to Balkan countries such as Albania, North Macedonia, and Bosnia and Herzegovina when calculating the average values (between the years 2010 and 2020) for various ICTs variables (e.g., 4G coverage, Internet users). The HCA of recent years, like 2020, shows the same picture. This means that there are some similar patterns of ICTs usage and investment in these countries. At the same time, an oil-rich country like Azerbaijan could be comparable to the leading Balkan countries like Greece, Romania, Slovenia, etc. While this gives the Azerbaijani government food for thought, the findings also highlight the potential for cooperation and knowledge sharing between Azerbaijan and the Balkan countries in the field of ICTs, as they can learn from each other's experiences and work together to further improve their respective ICTs sectors.
Conference: 3rd International Conference, Shaping the Future: Multidisciplinary Approaches to Digitalization and Economic Growth
Keywords: 330; Azerbaijani economy; Balkan countries; hierarchical cluster analysis; information communication technologies; technological change